Causes of Blindness and Visual Impairment Among Children Studying in Schools for the Blind in Central Development Region of Nepal - Shrestha, Jyoti Baba; Adhikari, Pragati Gautam; Shrestha, Gauri Shankar (Nepalese Medical Journal, 2021)
Introduction: This study was done to find out the causes of visual impairment in students studying in schools for the blind in the central development region of Nepal. Materials and Methods: The study was done in six schools for the blind in the central development region of Nepal. It was conducted by a team of Eye care professionals using standard eye examination protocols of the World Health Organization Prevention of Blindness Program in the year 2009. Results: A total of 133 students (5 - 21 years age group) enrolled in six schools for the blind were examined. 52.6% of children were visually impaired at birth and 12% developed vision impairment within one year of age. Twenty-one students (15.8%) had mild visual impairment, 5 students (3.8%) had severe visual impairment and 101 students (76%) were blind. The main cause of vision impairment was found to be lens-related anomaly 23.3% and retinal diseases, 18% followed by corneal lesions, 16.5%, and problems with the whole globe, optic nerve, and glaucoma accounting for 12.03%, 11.3%, and 7.5% respectively. The etiology could not be identified in 48.1% followed by hereditary causes (31.6%) and childhood factors (12%). Of the total students examined, 37.6% were visually impaired due to avoidable causes; preventable in 22.6% and treatable in 15% of cases. Conclusions: A high proportion of childhood blindness in schools for the blind in the central development region of Nepal is avoidable.